Organizational Studies: A Complement to the Study of Social Management (2019)
The article presents a reflection resulting from the PhD project “Construction intersubjective social management in the city of Medellin”, on the main aspects that turn the organizational studies into a complement in order to advance in the field of social management, addressed by tradition from the public. The article suggest how these aspects, which have an interdisciplinary perspective and look beyond the organization towards the study of phenomena different cultural, political, economic, social, among others, and whose nature is apparently non organizational, contribute to the conceptualization of social services management public which is not centered on the action of a single organization, but on the whole of the associations belonging to the civil society. In order to account for this, the article explains what is the social management, then discusses some of the main contributions made by the organizational theories, emphasizing aspects that give rise to organizational studies; after that, the article presents the contributions made by the organizational studies to the research in social management; finally, the conclusions are presented.